Theoretical and Methodological Framework for the Relationship Between State Sovereignty and International Legal Responsibility - Melnychenko, Vladyslav (Problems of legality, 2026)
This scientific publication explores the theoretical and methodological foundations underlying the relationship between the interconnected concepts of state sovereignty and international responsibility. The relevance of this research stems from the need for effective regulation of states’ international legal responsibility. The article aims to identify the doctrinal basis for the relationship between holding states accountable under international law for violations of the established legal order and the protective function of sovereignty, which can sometimes shield violators of international norms from legal consequences. To achieve this, the article employs a range of general scientific and specialized methods, including comparison, reductionism, dialectical analysis and synthesis, the comparative legal method, as well as formal and logical legal methods. The article explores the role of state responsibility within the framework of international law. It highlights that, at present, international legal scholarship maintains notably conservative approaches to regulating relations between states. As a result, the application of international legal responsibility for states encounters several challenges, especially regarding the unique interpretations of state sovereignty. Applying the principle of reductionism, sovereignty is viewed as the embodiment of the key qualities of legal personality. Thus, a sovereign entity’s (state’s) capacity to assume responsibility for breaches of international law is considered an expression of its sovereignty, which includes both rights and obligations. The doctrine of state sovereignty is shown to be dynamic, leading to its continual transformation within legal reality. This dynamism challenges the concept of "limited" sovereignty, as its proponents often disregard earlier iterations and deny the doctrine's evolution. Recognizing this opens new avenues for research, particularly in relation to how states are held accountable under international law.